2009
DOI: 10.1515/znc-2009-9-1023
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Enolase in the Subfractions of a Breast Cancer Cell Line

Abstract: Cell fractionationCells were washed twice in cold PBS and then resuspended in hypotonic buffer containing 10 mM Localization of Enolase in the Subfractions of a Breast Cancer Cell LineEwa Seweryn*, Jadwiga Pietkiewicz, Iwona S. Bednarz-Misa, Ireneusz Ceremuga, Jolanta Saczko, Julita Kulbacka, and Andrzej Gamian Enolase detected on the cell surface may be a receptor for certain ligands, especially for plasminogen. It is important for the pathogen invasiveness and in the development of a tumour. Therefore, we so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Most probably, these proteins possess auxiliary function. Enolase is a glycolytic enzyme present in eukaryotes and prokaryotes (Seweryn et al 2007, 2009). In humans, besides catalyzing glycolysis and gluconeogenesis, it composes membranes of epithelial and endothelial cells, monocytes, leucocytes, and neutrophiles where it acts as a receptor of human plasminogen (Pancholi and Fischetti 1998; Pancholi 2001; Lopez-Alemany et al 2003; Diaz-Ramos et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most probably, these proteins possess auxiliary function. Enolase is a glycolytic enzyme present in eukaryotes and prokaryotes (Seweryn et al 2007, 2009). In humans, besides catalyzing glycolysis and gluconeogenesis, it composes membranes of epithelial and endothelial cells, monocytes, leucocytes, and neutrophiles where it acts as a receptor of human plasminogen (Pancholi and Fischetti 1998; Pancholi 2001; Lopez-Alemany et al 2003; Diaz-Ramos et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ENOA is localized on the cell surface of PDAC, breast and lung cancers [67,154,172,189] (Table 3), while in melanoma and NSCLC it is also secreted by exosomes [190,191]. On cell surfaces, ENOA is part of a multi-protein complex, together with uPA receptor (uPAR), integrins and certain cytoskeletal proteins, collectively known as a metastasome , responsible for adhesion, migration and proliferation, as clearly demonstrated in ovarian cancer cells [192].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed on the surface of eukaryotic cells such as macrophages, neutrophils, endothelial, neuronal and tumor cells (32). Moreover, it is important in myogenesis, tumorgenesis and angiogenesis (32), as well as for pathogen invasiveness and the development of tumors (33). It has been shown that enolase mediates the activation of enzymes involved in the invasion of tissues by pathogens and tumor cells, as well as in the evasion of host immune responses (34), and that it is sensitive to fluoride (35).…”
Section: Discussionmentioning
confidence: 99%